Assessing the accuracy of a point-of-care analyzer for hyperlipidaemia in western Kenya. - Park, Paul H.; Chege, Patrick; Hagedorn, Isabel C.; Kwena, Arthur; Bloomfield, Gerald S.; Pastakia, Sonak D. (Tropical Medicine & International Health, 2016)
Objectives: The prevalence of hyperlipidaemia, along with other non-communicable diseases, is on the rise in low- and middle-income countries. CardioChek PA is a point-of-care lipid measuring device, which seeks to overcome laboratory-based diagnostic barriers by providing immediate results without dependency on significant laboratory infrastructure. However, it has not been validated in Kenya. In this study, we assess the accuracy of CardioChek PA with respect to the gold standard laboratory-based testing.Methods: In Webuye, Kenya, two blood samples were collected from 246 subjects to simultaneously measure the lipid levels via both CardioChek PA and the gold standard. All subjects were adults, and geographic stratified sampling methods were applied. Statistical analysis of the device's accuracy was based on per cent bias parameters, as established by the United States National Institutes of Health (NIH). The NIH recommends that per cent bias be ≤±3% for low-density lipoprotein (LDL) cholesterol, ≤±5% for high-density lipoprotein (HDL) cholesterol, ≤±5% for total cholesterol (TC) and ≤±4% for triglycerides (TG). Risk group misclassification rates were also analysed.Results: The CardioChek PA analyzer was substantially inaccurate for LDL cholesterol (-25.9% bias), HDL cholesterol (-8.2% bias) and TC (-15.9% bias). Moreover, those patients at higher risk of complications from hyperlipidaemia were most likely to be misclassified into a lower risk category.Conclusion: CardioChek PA is inaccurate and not suitable for our clinical setting. Furthermore, our findings highlight the need to validate new diagnostic tools in the appropriate setting prior to scale up regardless of their potential for novel utility.